2009
DOI: 10.1021/jo900801c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pentahydroxylated Pyrrolizidines and Indolizidines

Abstract: 1,3-Dipolar cycloaddition reaction of nitrone 7 and chemo-enzymatically obtained alkenediols 12 and 13 has been used in the synthesis of pentahydroxylated pyrrolizidines (8 and 10) and indolizidines (9 and 11). The pyrrolizidinic and indolizidinic skeletons were built after internal n-alkylation of the suitably functionalized pyrroloisoxazolidine intermediates obtained by the necessary protecting group manipulations. This method expands the scope of cycloaddition reactions in the synthesis of new and highly po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Our groups have a longstanding interest in the total synthesis of pyrrolizidine and indolizidine alkaloids and analogues 6,7. In particular, Goti and co‐workers have widely exploited the use of polyhydroxylated nitrones as dipoles in 1,3‐dipolar cycloaddition chemistry6a,6b,4e and as electrophiles towards organometallics,6c,6d whereas Tamayo and co‐workers have recently expanded the scope of cycloadditions for the synthesis of unnatural pentahydroxypyrrolizidines and ‐indolizidines with hydroxymethyl groups at C5 by use of chemoenzymatically prepared but‐3‐ene‐1,2‐diol derivatives as dipolarophiles 8…”
Section: Introductionmentioning
confidence: 99%
“…Our groups have a longstanding interest in the total synthesis of pyrrolizidine and indolizidine alkaloids and analogues 6,7. In particular, Goti and co‐workers have widely exploited the use of polyhydroxylated nitrones as dipoles in 1,3‐dipolar cycloaddition chemistry6a,6b,4e and as electrophiles towards organometallics,6c,6d whereas Tamayo and co‐workers have recently expanded the scope of cycloadditions for the synthesis of unnatural pentahydroxypyrrolizidines and ‐indolizidines with hydroxymethyl groups at C5 by use of chemoenzymatically prepared but‐3‐ene‐1,2‐diol derivatives as dipolarophiles 8…”
Section: Introductionmentioning
confidence: 99%
“…The first total synthesis of hyacinthacine C 2 and proposed structure of C 3 and their C5 epimers 10 and 11, respectively by Yoda et al [60] Scheme 2. The total synthesis of unnatural hyacinthacine C 2/3 analogues 20 and 24 by Tamayo et al [71]…”
Section: Tamayo Et Al 2010mentioning
confidence: 99%
“…At around the same time as Yoda et al , Tamayo and co-workers published their work detailing the synthetic approach to making analogues of hyacinthacines C 2 / 3 from the arabinose derived nitrone 12 [ 71 ] (Scheme 2 ). Their synthesis began with the 1,3-dipolar cycloaddition of the chemoenzymatically prepared 3-buten-1,2-diol derivatives 13a or 13b to nitrone 12 to afford cycloadducts 14 or 15 , respectively.…”
Section: Hyacinthacine Alkaloidsmentioning
confidence: 99%
“…The authors showed that lipase-mediated resolution was effective for the Hyacinthacine C 2/3 analogues were prepared by nitrone cycloaddition of 402 with allylic alcohol 468 (/ 466, Scheme 71) or allylic acetate 469 (en route to 470). 164 The dipolarophiles were obtained by lipase mediated kinetic resolution of racemic 3-buten-1,2-diol and their cycloadditions found to afford predominantly one diastereromer in each case. From isoxazolidine 466, a standard sequence was followed (sulfonylation, N-O reduction and cyclisation, then two deprotection steps) to give pyrrolizidine 467.…”
Section: Hyacinthacinesmentioning
confidence: 99%